Value Added Statement and ESG Information - Checon, Bianca Quirantes (2023)
This research aimed to investigate how the Value-Added Statement (VAS) may contribute as a financial information disclosure source with a social objective compared to the Environmental, Social, and Governance (ESG) measures available in the market. For this, information was collected related to the value-added distributed by 388 Brazilian companies listed on B3 from 2010 to 2022, as well as the respective aggregate ESG indices by pillars and the score of the Refinitiv Eikon database. The factor analysis indicated that the categories of distributed value added clustered only with the Governance pillar, not being related to the social and environmental pillars. However, through regressions with control variables and fixed effects of company and year, it was found that companies with higher levels of value distribution to creditors, which occurs mainly in the form of interest payments, have lower scores in the Environmental pillar, with no relationship between the other variables and pillars. The results indicate, therefore, that the information in the VAS needs to be complemented by the constants in the ESG scores.